Use of Hydrogels for Seawater Desalination Processes: A Patent Landscape Report - Ahmed Fatimi (Environmental Sciences Proceedings, 2023)
This patent landscape report encapsulates the state by introducing what has been invented concerning hydrogels for seawater desalination processes. As a result, 81 patent documents were found, and 62% of all patent documents have been published during the last three years. According to the findings, China was ranked as the first jurisdiction, and the most prolific patenting companies are from China and the United States, while William Marsh Rice University (United States) and Tianjin Polytechnic University (China) are the academic institutions leading the way. The patent classifications indicate that most inventions are intended for the treatment of seawater (e.g., desalination); processes specially adapted for manufacturing semi-permeable membranes for separation processes; and the treatment of water using ion-exchange sorbent compositions, dialysis, osmosis, or reverse osmosis. According to the knowledge clusters and expert driving factors in this patent landscape analysis, research and development are centered on methods and apparatus for desalination, which are the focus of the majority of patents, as well as macromolecular gels and synthetic macromolecular substances.